Microglia states and nomenclature: A field at its crossroads - Lynch, Marina; Cunningham, Colm (My University, 2022)
Microglial research has advanced considerably in recent decades yet has been constrained by a rolling series of dichotomies such as ‘‘resting versus activated’’ and ‘‘M1 versus M2.’’ This dualistic classification of good or bad microglia is inconsistent with the wide repertoire of microglial states and functions in development, plasticity, aging, and diseases that were elucidated in recent years. New designations continuously arising in an attempt to describe the different microglial states, notably defined using transcriptomics and proteomics, may easily lead to a misleading, although unintentional, coupling of categories and functions. To address these issues, we assembled a group of multidisciplinary experts to discuss our current understanding of microglial states as a dynamic concept and the importance of addressing microglial function. Here, we provide a conceptual framework and recommendations on the use of microglial nomenclature for researchers, reviewers, and editors, which will serve as the foundations for a future white paper.
PUBLISHED
cited By 25